Contemporary and emerging fisheries in The Bahamas—Conservation and management challenges, achievements and future directions - Krista D. Sherman; Aaron D. Shultz; Craig P. Dahlgren; Claire Thomas; Edward Brooks; Annabelle Brooks; Daniel R. Brumbaugh; Lester Gittens; Karen J. Murchie (Fisheries Management and Ecology, 2018)
The harvest of marine resources has long‐standing cultural and economic importance to The Bahamas and other small island developing states. Tourists and residents place a demand on local marine resources, particularly Caribbean spiny lobster , Panulirus argus (Latreille), queen conch, Lobatus gigas (Linnaeus) and Nassau grouper, Epinephelus striatus (Bloch), and many fishery products are also sold on the global market. Illegal, unreported and unregulated fishing coupled with inadequate regulations and enforcement are the main factors contributing to the decline of Bahamian fisheries along with other anthropogenic impacts. This article reviews the status of fisheries management in The Bahamas using economically and ecologically important species as case studies to highlight conservation successes, knowledge gaps and deficiencies in existing management approaches. The review concludes with an examination of how emerging fisheries and improved conservation management strategies have the potential to improve economic and food security throughout the archipelago.